Corporate social responsibility's relationship with marketing and financial performance of agricultural companies: a case study in East Java, Indonesia - Evi Thelia Sari; Rika Yuliastanti; Parwita Setya Wardhani (Universitas Lancang Kuning, 2023)
Agricultural companies that produce utilitarian products must prioritize corporate social responsibility (CSR) efforts to uphold their reputation (Rep) and ensure long-term sustainability through superior performance. This study aims to examine the relationship between corporate responsibility and corporate financial and marketing performance, with differentiation strategy (Diff), firm size (FS), internationalization (Int), perceived external pressure (PEP), and altruism (Alt) acting as drivers of CSR initiatives. Employing a quantitative research approach, this study utilized the fuzzy inference system (FIS) to identify the predictive relationships between variables. Purposive sampling was employed to select five legally incorporated agricultural companies in East Java. The findings indicated that, at specific value thresholds, Diff, FS, Int, PEP, or Alt could serve as drivers of CSR efforts and were associated with corporate financial performance (CFP) and corporate marketing performance (CMP) from the perspectives of CSR, Rep, and PEP. The FIS output models, aligned with the proposed hypotheses, demonstrated that certain values of these input variables positively influence the direction of the output variables. Therefore, company policymakers should carefully consider the value levels of these variables and strive to maintain them to enhance CSR efforts and improve financial and marketing performance effectively. These factors were vital for the sustainability of agricultural companies in East Java.